Robotic versus open pancreaticoduodenectomy in elderly patients: a propensity score–matched analysis. Issue 3 (March 2023) - Mederos, Michael A.; Starr, Savannah; Park, Joon Y.; King, Jonathan C.; Tomlinson, James S.; Hines, O.J.; Donahue, Timothy R.; Girgis, Mark D.
Abstract: Background: Pancreaticoduodenectomy (PD) is complex procedure with high morbidity in the elderly. This retrospective study aimed to compare post-operative outcomes in patients ≥75 years of age who underwent robot-assisted (RA)PD and open PD. Methods: We analyzed 2502 patients ≥75 years of age who underwent PD from 2015 to 2018 in the National Surgical Quality Improvement Program (NSQIP) database. RAPD and open PD patients were propensity score matched 1:5 to assess the 30-day outcomes of interest: postoperative complications, length of stay, discharge destination, and readmissions. Results: Of 725 matched patients, 110 underwent RAPD, 615 OPD, and 12 were converted to an open operation. Post-operative outcomes were largely similar between cohorts. RAPD was associated a shorter length of stay (median 8 days, interquartile range [IQR] 6 to 11) than OPD (median 8 days, IQR 7 to 13) (p = 0.003). However, RAPD was associated with more readmissions (28.1% vs. 17.7%; p = 0.02). Conclusions: RAPD in patients ≥75 years of age appears to be safe and has a similar complication profile to open PD. Randomized or well-designed prospective matched studies are needed to confirm these findings.